Does p53 codon 72 polymorphism have a prognostic value in carcinoma of the vulva and vagina? - Qvick, Alvida; Sorbe, Bengt; Helenius, Gisela; Karlsson, Mats G.; Lillsunde Larsson, Gabriella (Medical oncology (Northwood, London, England), 2017)
Human papilloma virus (HPV) is considered to be responsible for a large part of vaginal and vulvar carcinomas, and the p53 codon 72 polymorphism has been implicated in susceptibility to cancer induced by this virus, but with contradicting results. In this study, we have investigated the prognostic value of the codon 72 polymorphism by real-time PCR (qPCR) in two cohorts of vaginal ( n = 66) and vulvar ( n = 123) carcinomas. In vaginal carcinoma, arginine homozygous patients were significantly associated with a higher primary cure rate ( p = 0.023) but also associated with a higher recurrence rate ( p = 0.073), significant at distant locations ( p = 0.009). No significant differences were found in overall survival rate ( p = 0.499) or cancer-specific survival rate ( p = 0.222). A higher frequency of arginine homozygosity was noted in HPV-positive tumors ( p = 0.190) in comparison with HPV-negative tumors. In vulvar carcinoma, the genotype homozygous for arginine was significantly associated with a larger tumor size at diagnosis in the entire cohort ( p = 0.015) and a lower cancer-specific survival rate ( p = 0.024) compared with heterozygous (arginine/proline) in HPV-negative tumors. Our results indicate that the relation between HPV and the p53 codon 72 polymorphism is complex and the significance and mechanisms responsible for this relationship need to be further elucidated.